Governance and Transition Politics in Kenya - (:unkn) unknown (My University, 2007)
A rebviw of the book edited by Peter Wanyande, Mary Omosa, Ludeki Chweya Nairobi, University of Nairobi Press, 2007 S peaking freely about politics in Kenya is no longer the gamble that it was in the recent 1990s, where the slightest public deviance within the civil society could have disastrous consequences for those that held such contentious or 'dissident' views. Although the current situation cannot be termed as totally open, it should be noted that there exists a real spread of freedom of expression in the media, among the blossoming non-governmental organisations (on human rights, conflict management, risk control etc), as much as in academic circles. In the latter, lecturers/researchers, be they in Kenya or abroad, no longer hesitate to offer strong, hard-hitting views on the political situation. This has been going on for several years now. Governance and Transition Politics in Kenya belongs to the body of published works whose resolute and well-argued views provides a framework for critical examination of the political regime, despite the self-same regime being the one that made this freedom possible. It just goes to show that the desire for democracy within civil society can only go unresolved in view of the mimicry which is often denied by the highest level of the state organs. This book aims at explaining why the smooth transition from the Moi era—who only accepted multipartyism and pluralist elections under the combined pressure of an angered society and incensed donors—to the Kibaki regime delayed in delivering the promised results. It refers to a " delayed, frustrated, indirect " transition and an almost complete failure. Admittedly, in reading Peter Anyang' Nyong'o's interpretations in the introductory pages, one could ask if drawing such conclusions for so short a period is not going too far. Nevertheless, the arguments given by the different contributors have the merit of a constant to and fro between the pre-colonial, colonial an
Keywords: African Research